A cleavable self‐assembling tag strategy for preparing proteins and peptides with an authentic N‐terminus. Issue 6 (15th May 2017) - Zhao, Qing; Zhou, Bihong; Gao, Xianxing; Xing, Lei; Wang, Xu; Lin, Zhanglin
Abstract: Recombinant protein expression and purification remains a central need for biotechnology. Herein, the authors report a streamlined protein and peptide purification strategy using short self‐assembling peptides and a C‐terminal cleavage intein. In this strategy, the fusion protein is first expressed as an aggregate induced by the self‐assembling peptide. Upon simple separation, the target protein or peptide with an authentic N‐terminus is then released in the solution by intein‐mediated cleavage. Different combinations of four self‐assembling peptides (ELK16, L6 KD, FK and FR) with three inteins ( Sce VMA, Mtu ΔI‐CM and Ssp DnaB) were explored. One protein and two peptides were used as model polypeptides to test the strategy. The intein Mtu ΔI‐CM, which has pH‐shift inducible cleavage, was found to work well with three self‐assembling peptides (L6 KD, FR, FK). Using this intein gave a yield of protein or peptide comparable with that from other more established strategies, such as the Trx‐strategy, but in a simpler and more economical way. This strategy provides a simple and efficient method by which to prepare proteins and peptides with an authentic N‐terminus, which is especially effective for peptides of 30‐100 amino acids in length that are typically unstable and susceptible to degradation in Escherichia coli . Abstract : A streamlined protein and peptide purification strategy using short self‐assembling peptides and a C‐terminal cleavage intein is described. This strategy provides a simple and efficient method by which to prepare proteins or peptides with their authentic N terminus, which is especially effective for peptides of 30‐100 amino acids (aa) in length that are typically unstable and susceptible to degradation in Escherichia coli .